Alaş Orda Dönemi Kazak Edebiyatında Aydınlanma ve Millî Bilincin Yeniden İnşası - Kapağan, Enver; Bacaklı, Yılmaz (Journal of History Culture and Art Research, 2020)
Enlightenment and Reconstruction of National Awareness in Kazakh Literature During Alash Orda Era Abstract Kazakh Turks have lived in the same geography since ancient times. This situation brings about the formation of a rich and deep-rooted tradition. Kazakh, like all other Turkish communities, was accepted as a part of the common literature and culture belonging to the Turkish world, and in particular, a Kazakh oral and written literature started to be formed, as they existed in the history scene with their own names. In Kazakh Turks, literature, which continued its existence orally until the 20th century, continued its development both verbally and in writing afterwards. Especially in the development of written literature in the last century, the identification and exploitation policies of the Russians towards Turkish communities have an important effect. Literature, which is one of the most effective tools in the formation and development of national identity, is effectively used by intellectual names against these policies carried out by the Russians. Thanks to the educational environment developed with the pressure of Russian politics aimed at eliminating Kazakh identity and culture, intellectual names which grown from the Kazakh society begin to fight against Russian politics with their pens. This intellectual movement determines ‘Alash Khan’, who is an important figure of independence and unity in the history of Kazakh Turks, as their names and slogans. Using this name and slogan, they aim to hold together the national and spiritual values that take place in the historical roots of the Kazakh people. The intellectuals of the ‘Alash Orda’ period work to build a national consciousness that can meet the needs of the era without departing from its historical roots, based on the ideas and works of art of both Eastern and Western cultures. In this article, the idea of the Alash Orda movement, which has an important place in Kazakh enlightenment, and the process of ‘Enlightenment and Reconstruction of National Awareness in Kazakh Literature during Alash Orda Period’ shaped by political and cultural stance will be discussed. Alaş Orda Dönemi Kazak Edebiyatında Aydınlanma ve Millî Bilincin Yeniden İnşası Öz Kazak Türkleri tarihin eski devirlerinden beri aynı coğrafyada yaşamlarını sürdürürler. Bu durum kendilerine ait zengin ve köklü bir geleneğin oluşmasını da berberinde getirir. Kazak adı ile var oldukları döneme kadar geçen süreçte diğer bütün Türk toplulukları gibi Kazaklar da Türk dünyasına ait ortak edebiyat ve kültürün bir parçası olarak kabul görürken kendi adları ile tarih sahnesinde var olmaları ile birlikte özelde de bir Kazak sözlü ve yazılı edebiyatı teşekkül etmeye başlar. Kazak Türklerinde XX. yüzyıla kadar daha çok sözlü olarak varlığını devam ettiren edebiyat, sonraları hem sözlü hem de yazılı olarak gelişimini sürdürür. Özellikle son yüzyılda yazılı edebiyatın gelişmesinde Rusların Türk topluluklarına dönük kimliksizleştirme ve sömürme politikalarının önemli bir etkisi olur. Milli kimliğin oluşup gelişmesinde en etkili araçlardan biri olan edebiyat, Rusların yürüttüğü bu politikalara karşı aydın isimler tarafından etkin bir biçimde kullanılır. Kazak kimliğini ve kültürünü ortadan kaldırmaya dönük Rus siyasetinin baskısıyla gelişen eğitim ortamı sayesinde Kazak toplumu içerisinden yetişen aydın isimler, Rus siyasetine karşı kalemleriyle mücadeleye başlar. Bu aydın hareketi Kazak Türklerinin tarihinde bağımsızlığın ve birliğin önemli bir figürü olan ‘Alaş Han’ı kendilerine isim ve slogan olarak belirler. Bu isim ve sloganı kullanarak Kazak halkının tarihî köklerinde yer alan millî ve manevî değerler etrafında bir arada tutmayı hedeflerler. ‘Alaş Orda’ dönemi aydınları hem Doğu hem de Batı kültürüne ait düşünce ve sanat eserlerinden hareketle tarihî köklerinden kopmadan çağın ihtiyaçlarına cevap verebilecek millî bir bilinç inşa etmek için çalışır. Bu makalede Kazak aydınlanmasında önemli bir yer tutan Alaş Orda hareketinin ortaya koyduğu fikri, siyasi, kültürel duruş ile şekillenen ‘Alaş Orda Dönemi Kazak Edebiyatında Aydınlanma ve Millî Bilincin Yeniden İnşası’ süreci ele alınacaktır.